Revealed wisdom and inaugurated eschatology in ancient Judaism and early Christianity - Macaskill, Grant (Supplements to the Journal for the study of Judaism ;, 2007)
Examines four texts such as: "1 Enoch", "4QInstruction", "Matthew" and "2 Enoch" and argues that in each the revealing of wisdom to an elect group inaugurates the eschatological period. This text challenges the simplistic redactional assumptions of certain New Testament scholars.